2020
DOI: 10.2147/ott.s240734
|View full text |Cite
|
Sign up to set email alerts
|

<p>KIF4A Promotes Clear Cell Renal Cell Carcinoma (ccRCC) Proliferation in vitro and in vivo</p>

Abstract: These authors contributed equally to this workPurpose: To evaluate the expression in human clear cell renal cell carcinoma (ccRCC) tissues and explore the effects of kinesin family member 4A (KIF4A) on ccRCC progression. Methods: GEPIA was used to evaluate the mRNA levels of KIF4A in human ccRCC tissues from TCGA database, and Immunohistochemistry (IHC) assays were performed to assess its expression in human ccRCC tissues collected in our hospital. The clinical-pathological analysis was performed to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
2
3
0
Order By: Relevance
“…* P<0.01. KIF4A expression is involved in multiple human cancer, including hepatocellular carcinoma, glioblastoma, oral cancer, lung cancer, breast cancer, colorectal cancer and clear cell renal cell carcinoma [29][30][31][32][33]. Consistent with previous observations, enhancive expression of KIF4A has been observed in 71% of PCa patients compared with healthy samples [36].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…* P<0.01. KIF4A expression is involved in multiple human cancer, including hepatocellular carcinoma, glioblastoma, oral cancer, lung cancer, breast cancer, colorectal cancer and clear cell renal cell carcinoma [29][30][31][32][33]. Consistent with previous observations, enhancive expression of KIF4A has been observed in 71% of PCa patients compared with healthy samples [36].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, we used GEPIA online tool to analyze KIF4A expressions in other malignancies, and found that the relative KIF4A mRNA levels were higher in specific tumors, compared with normal tissue. Recent studies have demonstrated that abnormal KIF4A expression is involved in the progressions of multiple human cancers [15,17,18,20,32,33]. These results support the suggestion that KIF4A may serve as a general oncogene.…”
Section: Discussionsupporting
confidence: 74%
“…Given that most patients with ccRCC are not sensitive to chemotherapy or radiation, surgical treatment has remained most effective [ 5 , 6 ]. Thus, exploring the molecular mechanisms underlying the development of ccRCC and identifying effective treatment strategies to improve the survival rate of patients with ccRCC hold considerable clinical value.…”
Section: Introductionmentioning
confidence: 99%
“…KIF4A is overexpressed in most tumors, but also low in a minority [ 20 ]. Yang et al, found that KIF4A is abnormally highly expressed in human clear cell renal cell carcinoma tissues and can act as a tumor-inducing gene [ 21 ]. Zhu et al, proposed that enhanced KIF4A expression in osteosarcoma predicts poor prognosis and promotes tumor growth by activating the MAPK pathway [ 22 ].…”
Section: Discussionmentioning
confidence: 99%